Deciduous teeth eruption in full and mosaic type of Down’s Syndrome patient - Willyanti Sjarif (Dental Journal (Majalah Kedokteran Gigi), 2005)
The purpose of this study was to examined the correlation of deciduous teeth eruption with the karyotipe of) Down’s Syndrome patient. Full and Mosaic karyotype in Down’s Syndrome (DS) patients have different prognostics. A total of 33 DS patients constituted of 23 full and 10 mosaics were enrolled in this cross sectional study. The Chi-square statistical test was utilized to analyze the data. The result revealed that a full trisomy DS patients had their deciduous teeth erupted in 13-18 months old while a mosaic DS patients in 8-12 months old. The conclusion affirmed that the deciduous teeth eruption in mosaic DS patients is earlier than full DS patients (p = 0.002).